Influence of internal excitation and boxbody flexibility on the vibration of high-speed train gearboxes - YU Hongda; LIU Jiahui; HUANG Zhihui; TIAN Mingjie (机车电传动)
During the operation of high-speed trains, the loads on the gearbox are very complex, and cracks often occur in the boxbody. To ensure the service safety of the gearbox body, a dynamic model of high-speed trains with a gear transmission system was established based on SIMPACK. Comparative analysis of the vibration response of the gearbox rigid body at speeds of 200 km/h, 250 km/h, 300 km/h and 350 km/h was conducted, considering only track excitation and both gears internal excitation and track excitation. In addition, a rigid-flexible coupling dynamic model of a high-speed train considering a flexible gearbox body was established to analyze its impact on the vibration calculation results of the gearbox body. The results indicate that the internal excitation of the gearbox has a little impact on the lateral vibration acceleration of the gearbox body, but at the rotational frequency of the driving gear and the engagement frequency of the gears, the vertical vibration acceleration of the gearbox body will exhibit a peak value, which significantly increases its root mean square value, with an average increment of 4.8 m/s2. At a speed of 200 km/h, the resonance is caused by the similarity between the rotational frequency of the driving gear and the modal frequency of the gearbox pitching, resulting in a very significant increase in the root mean square value of the vertical vibration acceleration of the gearbox body. Therefore, when analyzing the vibration of the gearbox body, the internal excitation of the gearbox cannot be ignored. The flexibility of the gearbox body has a little impact on the lateral vibration acceleration of the gearbox body when considering the internal excitation, but it will reduce the root mean square value of the vertical vibration acceleration to some extent. The average reduction after the speed reaches 300 km/h is large, reaching 2.72 m/s2.